Multidisciplinary management of surgery and postoperative recurrence in stage IV gallbladder cancer following conversion therapy: a case report - Cheng, Junfeng; Li, Xuemin; Ren, Chao; Yu, Shian; Huang, Hongwei; Zhou, Shishi; Dai, Jianji (Frontiers in Oncology, 2026)
A 61-year-old female patient presented with a 10-day history of right upper abdominal pain and was subsequently diagnosed with stage IV gallbladder cancer based on preoperative imaging and pathological evaluation. Following multidisciplinary discussion, a triple-agent combination therapy was initiated. Although the patient developed severe grade II cutaneous toxicity during treatment, a significant clinical response was achieved, and symptoms were effectively relieved with supportive management. After four months of conversion therapy, the patient underwent successful radical surgical resection. Five months postoperatively, isolated hepatic metastases were identified, and a multidisciplinary team subsequently recommended radiofrequency ablation. The patient is currently receiving maintenance therapy with immune checkpoint inhibitors. At the most recent follow-up, the patient remains disease-free, with an overall survival of 18 months.